Fikih Perbandingan Tentang Syarat Dan Rukun Jual Beli serta Relevansinya dengan Jual Beli Modern - Deddi Ajir (Risalah Iqtishadiyah, 2022)
Buying and selling online is currently carried out without meeting directly between the seller and the buyer. Instead, it is done online by providing pictures of descriptions and descriptions of goods to buyers through social media and marketplace applications. So that in practice the buyer only sees a description of the sales he will buy and the buyer cannot see directly the goods he will buy so that it is most likely that when the goods arrive in the hands of the buyer, the picture seen before does not match the goods received. This study aims to determine the law of buying and selling online in the Islamic legal system and the differences between buying and selling in the past and present. This type of research is library research. This research is descriptive in nature and the data collection method uses library research techniques. Data from friends is described descriptively and analyzed using a deductive way of thinking. The results of the study show that buying and selling online is permissible and legal to use. The difference between buying and selling then and now lies in the clarity of the bargaining process used.